The racial violence and gender oppression: Palestinian womens struggle based on selected novels by Sahar Khalifah - Jasim, Iman Naemah (2022)
The main objective of this research was to study racial violence and gender oppression in Sahar Khalifehs selected novels of Of Noble Origins (2012), The End of Spring (2007), The Inheritance (2005), The Image, and The Icon and the Covenant (2007). The research also followed a qualitative textual analysis to interpret the colonial confrontation between the Jewish persecutory occupation that represents the colonizers who oppress the Palestinian people, especially the women. Furthermore, gender oppression was interpreted to scrutinize the masculine ideology that marginalizes women in the Palestinian traditional society. Accordingly, three inextricable objectives were formulated in the course of the analysis. The first objective was to ascertain the extent of how the encounter with the Israeli racial violence affects the Palestinian women based on the novels by Sahar Khalifeh. The second objective was to examine how the Palestinian women resist the Jewish occupation in the selected novels. And the third objective was to investigate how the Palestinian women challenge and resist the patriarchal ideology of her society. As such, the research conducted a qualitative methodology that followed a close reading of female characters that suffer from colonial and patriarchal oppression. Additionally, postcolonial feminism was used as critical theory for the analysis. The research findings showed the exploration of Israeli racial violence and its resistance by Palestinian women. Another major finding demonstrated the Palestinian women as victims of the ideology of patriarchy and, as such, they attempt to challenge it in direct and indirect ways. In conclusion, the research implies that Israeli racial violence and gender oppression are major factors that have affected the Palestinian women. This led to the implications of the research which identified the Palestinian womens reaction to colonialism and patriarchy as a rejection determined resistance in order to guarantee their liberty and independence.